On the possibility for the resonance ELM-generation mechanism by the injection of the neutral particle beam in tokamak - Gordeev, A.V. (Вопросы атомной науки и техники, 2007)
It is known that in plasmas with a magnetic field the Hall electric field is generated at the expense of the charge separation on the magnetic Debye radius rB=|B|/(4pene). In addition, the plasma current equilibrium can arise, where the charged particles are drifting in the crossed electric and magnetic fields. Such a situation can be realized in tokamaks as a result of the ionization processes for the beams of the energetic neutral particles that are injected in tokamaks in order to increase the plasma density and temperature. In this presentation, the generation of the resonance instability for the azimuthal drifting flux of the ions and electrons crosswise to the strong magnetic field is considered. Відомо, що в плазмі з магнітним полем генерація холловського електричного поля за рахунок поділу зарядів відбувається на магнітному дебаєвському радіусі rB=|B|/(4pene). При цьому можливо утворення плазмової токової рівноваги, де заряджені частки дрейфують у схрещених електричному і магнітному полях. Така ситуація може бути реалізована в токамаках як наслідок процесів іонізації пучка енергійних нейтральних часток, інжектуємих у токамаки, з метою підвищення густини плазми і її температури. Розглянуто генерацію резонансної нестійкості азимутальних потоків іонів і електронів, що дрейфують поперек сильного магнітного поля. Известно, что в плазме с магнитным полем генерация холловского электрического поля за счёт разделения зарядов происходит на магнитном дебаевском радиусе rB=|B|/(4pene). При этом возможно образование плазменного токового равновесия, где заряженные частицы дрейфуют в скрещённых электрическом и магнитном полях. Такая ситуация может быть реализована в токамаках в результате процессов ионизации пучка энергичных нейтральных частиц, инжектируемых в токамаки, с целью увеличения плотности плазмы и её температуры. Рассмотрена генерация резонансной неустойчивости азимутальных потоков ионов и электронов, дрейфующих поперёк сильного магнитного поля.